Atmospheric interpretation of anomalous terrestrial emission serendipitously discovered in radioastronomy data at 1 Gigahertz - Burke-Spolaor, S.; Ekers, R.; Macquart, Jean-Pierre (2011)
A publication in the Astrophysical Journal [1] reported the discovery of swept-frequency, terrestrial emission in a search for astrophysical pulses. The emission's origin has yet to be determined; its attributes are atypical of known sources of terrestrial signals. We review the observed properties of the emission and present a simple model for a physical mechanism that could occur in the atmosphere to produce it. If this mechanism is the cause of the emission, its origin may lie in secondary effects of lightning production in the upper atmosphere. © 2011 IEEE.